An extension of the stochastic sewing lemma and applications to fractional stochastic calculus - Toyomu Matsuda; Nicolas Perkowski (Forum of Mathematics, Sigma, 2024)
We give an extension of Lê’s stochastic sewing lemma. The stochastic sewing lemma proves convergence in